DEATHS FROM PRESCRIPTION DRUG ABUSE IN FAISALABAD - Muhammad Naeem; Mobin Inam Pal; Humera Parveen et al. (Journal of University Medical & Dental College, 2018)
ABSTRACT: BACKGROUND: Prescription drugs are used to treat the humanity to reduce the ailments but these drugs when used irrationally either by the prescribing doctor or misused by the patient, may lead to death. OBJECTIVES: To analyze the most common prescription drugs which are being abused in the society and to create a check or ﬁlter for the prescriptions having narcotics and addictive drugs. Also, to suggest a control over the abusive prescription drugs by reviewing already existing legislations regarding sale and storage of abusive drugs. DESIGN: Non interventional (descriptive) study. PLACE AND DURATION OF STUDY: This study was conducted over a period of three years from st st1 January, 2014 to 31 December, 2016 at The Forensic Medicine & Toxicology Department, Punjab Medical College, Faisalabad. SAMPLE SIZE: 43 cases SAMPLING TECHNIQUE: Convenience Sampling. METHODOLOGY: Study included 918 autopsies conducted in the postmortem unit of Forensic Medicine & Toxicology Department, Punjab Medical College, Faisalabad. Out of these, samples in 252 cases were sent for chemical analysis to the Punjab Forensic Science Agency, Lahore out of which death in 43 cases was declared to have been caused by known drugs. RESULTS: Deaths from prescription drug abuse were 4.68% of the total autopsies done during this study period. Males were 81.39 % and female were 18.61%. The most aﬀected age group was between 21 to 40 years which totaled 69.7%. The most common Prescription drugs of abuse were chlorophenramine, morphine and diazepam. CONCLUSION: Among the most commonly prescribed drugs, chlorophenramine, morphine and diazepam were abused by the young generation. Prescribing doctor and pharmacist can play a key role to check and limitize the use of these drugs by proper counseling and making the person aware of the side eﬀects of these drugs and especially the prescribing doctors must rationalize the prescription of these narcotics drugs.